2003
DOI: 10.1037/0735-7028.34.5.491
|View full text |Cite
|
Sign up to set email alerts
|

What tests are acceptable for use in forensic evaluations? A survey of experts.

Abstract: When conducting a forensic evaluation, what psychological tests do experts consider acceptable to use? The answer is useful to psychologists making practice decisions but also to the courts, who rely on others' opinions to base one of the criteria for determining the admissibility of testimony. The author surveyed diplomates in forensic psychology (N = 64) regarding both the frequency with which they use and their opinions about the acceptability of a variety of psychological tests in 6 areas of forensic pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
155
0
16

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(173 citation statements)
references
References 18 publications
2
155
0
16
Order By: Relevance
“…Therefore, the data from our survey tells us more about test usage generally and less about tests used to evaluate specific forensic questions. Moreover, this survey also differs from that conducted by Lally (2003) that assessed opinions about acceptability rather than actual test usage by forensic psychologists. The overall response rate produced within various categories of testing shows that multiscale inventories such as the MMPI-2 were utilized by the largest proportion of respondents, with 131 (86% of all respondents) having reported use of one or more instruments in this category and 125 respondents (82.2%) having reported use of intellectual or achievement tests such as the Wechlser Intelligence scales.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Therefore, the data from our survey tells us more about test usage generally and less about tests used to evaluate specific forensic questions. Moreover, this survey also differs from that conducted by Lally (2003) that assessed opinions about acceptability rather than actual test usage by forensic psychologists. The overall response rate produced within various categories of testing shows that multiscale inventories such as the MMPI-2 were utilized by the largest proportion of respondents, with 131 (86% of all respondents) having reported use of one or more instruments in this category and 125 respondents (82.2%) having reported use of intellectual or achievement tests such as the Wechlser Intelligence scales.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, survey results have indicated that forensic psychology experts consider formal assessment tools to be highly desirable for use in forensic evaluations. In a survey of American Board of Forensic Psychologists diplomates regarding criminal evaluations, Lally (2003) found that a wide range of clinical and forensic assessment instruments were rated as being either "Recommended" or "Acceptable" by significant numbers of these professionals for evaluations of mental state at the time of the offense, risk for violence, risk for sexual violence, competency to stand trial, competency to waive Miranda Rights, and evaluations of malingering.…”
mentioning
confidence: 99%
“…In Psychology surveys of experts have been used to help select an appropriate assessment tool (e.g., in forensic situations: Lally, 2003); to understand the meaning of an everyday term (e.g., wisdom: Jeste et al, 2010); and to determine the content validity of items in a behavioral instrument (e.g., sluggish cognitive tempo, Penny et al, 2009). In an effort to determine what leaders in the field of IOR research explicitly and implicitly think about the phenomenon, we conducted a survey of experts that targeted some of the ambiguities surrounding IOR.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a notable expansion over time of forensically relevant assessment instruments and related research (Denney & Sullivan, 2008;Otto & Heilbrun, 2002 Archer et al, 2006;Jackson, Rogers, & Sewell, 2005;Pelfrey, 2004;Slick, Tan, Strauss, & Hultsch, 2004). A majority of diplomats in forensic psychology surveyed by Lally (2003) rated these instruments as acceptable for the assessment of malingering (with the exception of the M-FAST, for which no opinion was provided). Of interest from an historic perspective is that some tests (i.e., the MMPI-2 and the PAI) were originally designed for clinical use and not malingering detection, yet with time their role expanded into the forensic realm (Buchanan, 1994;Graham, Watts, & Timbrook, 1991;Rogers, Sewell, Morey, & Ustad, 1996).…”
Section: Introductionmentioning
confidence: 99%